KEGIATAN PENGEMBANGAN DIRI BERMAIN GITAR DI SMP NEGERI 30 PADANG - Fabi Yanda Deska; Yos Sudarman; Yensharti Yensharti (FBS Universitas Negeri Padang, 2018)
AbstractThis article aims to describe the activities of self development playing guitar in junior high 30-Country field. This type of research is qualitative research methods a descriptive analysis. The research was carried out at 22 students and coaches as its object, which is involved in the activity of self development playing guitar in junior high the land even semester Pasture 30 years teaching 2016/2017. The collection of data through observation, interview, documentation and library studies. The results showed that the implementation of the activities of the self development playing guitar in junior high 30 Pasture Land has been getting high from appreciative students, although at the time of exercise there are students who do not attend practice. As for the findings of the study showed that the implementation of the activities of the self development of guitar at the school had been done properly. It can be proved by ketercapaian students in material and latihanuntuk able to play guitar, guitar finger exercises, know, play tangganada, fingered and finally being able to play the song delman exceptional individually and groups.Keywords: activities, self development, guitar